1987
DOI: 10.1139/o87-110
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen sulfotransferase of mouse placenta: behaviour and characteristics during partial purification

Abstract: Mouse placental estrogen sulfotransferase (ST) was partially purified by fast protein liquid chromatography (FPLC) gel filtration in combination with FPLC anion exchange. Owing to the highly unstable nature of the enzyme, large increases in specific activity were not obtained. Storage of the ST in the presence of thiol groups at -20 degrees C stabilized the enzyme considerably. Forty-three percent of the cytosolic ST was bound to an Affi-Gel blue column and eluted as a broad peak at approximately 0.8 M NaCl. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Another publication reports a molecular mass of 31 kDa for an unstable oestrogen sulphotransferase from porcine uterus [23]. It has also been demonstrated that the corresponding enzyme in mouse placenta and uterus behaves as if it were a 29-30 kDa protein [7,8]. The presence of two forms of guinea pig adrenal oestrogen sulphotransferase during chromatofocusing parallels information obtained for the mouse placental enzyme [7] and for the guinea pig chorionic enzyme [10].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Another publication reports a molecular mass of 31 kDa for an unstable oestrogen sulphotransferase from porcine uterus [23]. It has also been demonstrated that the corresponding enzyme in mouse placenta and uterus behaves as if it were a 29-30 kDa protein [7,8]. The presence of two forms of guinea pig adrenal oestrogen sulphotransferase during chromatofocusing parallels information obtained for the mouse placental enzyme [7] and for the guinea pig chorionic enzyme [10].…”
Section: Discussionmentioning
confidence: 77%
“…The importance of these enzymes in this latter respect has been particularly noted in the mammalian intrauterine compartment [3][4][5][6]. Severe difficulties have been encountered in purifying and characterizing the poorly abundant oestrogen sulphotransferase(s) of intrauterine origin in small rodents including mouse [7,8] and guinea pig [9,10] during gestation. The reported presence of a hydroxysteroid sulphotransferase, which is particularly active toward pregnenolone [11], in the male Hartley guinea pig adrenal cortex, led us to enquire into the possible occurrence of an oestrogen sulphotransferase in that tissue, especially since the bovine adrenal gland contains an abundance of a stable enzyme of this type [12].…”
Section: Introductionmentioning
confidence: 99%